2007
DOI: 10.1523/jneurosci.2693-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Level Afferent Control of Growth Hormone-Releasing Hormone (GHRH) Neurons in GHRH–Green Fluorescent Protein Transgenic Mice

Abstract: The organization of the peptidergic neurons of the hypothalamic arcuate nucleus is not fully understood. These include growth hormonereleasing hormone (GHRH) neurons involved in growth and metabolism. We studied identified GHRH neurons of GHRH-green fluorescent protein transgenic mice using patch-clamp methods and focused on gender differences, which govern the physiological patterns of GHRH release. Both the spontaneous firing rates and the intrinsic properties of GHRH neurons were similar in males and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Moreover, in situ mRNA hybridization studies showed that GHRH neurons of the arcuate nucleus, the primary site of GHRH synthesis and storage in mice (35), also express M 3 mAChRs. In agreement with this observation, a recent electrophysiological study demonstrated that GHRH neurons are endowed with functional mAChRs, activation of which leads to enhanced action potential firing (36).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, in situ mRNA hybridization studies showed that GHRH neurons of the arcuate nucleus, the primary site of GHRH synthesis and storage in mice (35), also express M 3 mAChRs. In agreement with this observation, a recent electrophysiological study demonstrated that GHRH neurons are endowed with functional mAChRs, activation of which leads to enhanced action potential firing (36).…”
Section: Discussionsupporting
confidence: 64%
“…GABA also modulates GHRH neurons [27], so its potential involvement in the effect of ghrelin on GHRH neurons was studied. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…50). Mature (14-16 d in vitro) hippocampal neurons expressing the transfection marker ZsGreen were visualized and recorded with the patch-clamp technique, as previously described (51). After establishing the whole-cell configuration, MEA-TMA (100 μM) was briefly applied onto the neuron from a glass pipet, located at <100-μm distance from the cell body.…”
Section: Methodsmentioning
confidence: 99%